2013
DOI: 10.1016/j.celrep.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The Presenilin-1 ΔE9 Mutation Results in Reduced γ-Secretase Activity, but Not Total Loss of PS1 Function, in Isogenic Human Stem Cells

Abstract: Presenilin 1 (PS1) is the catalytic core of γ-secretase, which cleaves type-1 transmembrane proteins including the amyloid precursor protein (APP). PS1 also has γ-secretase independent functions and dominant PS1 missense mutations are the most common cause of familial Alzheimer’s disease (FAD). Whether PS1 FAD mutations are gain or loss-of-function remains controversial, primarily because most studies have relied on overexpression in mouse and/or non-neuronal systems. We used isogenic euploid human iPSC lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 51 publications
(68 reference statements)
8
137
1
5
Order By: Relevance
“…Drug development, and eventually drug treatment, may need to be individualized for specific APP mutations based on a better understanding of their individual downstream affects. The use of induced pluripotent stem cell (IPS)-derived neuronal patient lines and AD mutations introduced by genome editing in isogenic neuronal IPS lines (Israel et al, 2012;Kondo et al, 2013;Muratore et al, 2014;Shi et al, 2012;Woodruff et al, 2013;Yagi et al, 2011) could therefore act as a valuable new tool for future studies of these different ADs.…”
Section: Reviewmentioning
confidence: 99%
“…Drug development, and eventually drug treatment, may need to be individualized for specific APP mutations based on a better understanding of their individual downstream affects. The use of induced pluripotent stem cell (IPS)-derived neuronal patient lines and AD mutations introduced by genome editing in isogenic neuronal IPS lines (Israel et al, 2012;Kondo et al, 2013;Muratore et al, 2014;Shi et al, 2012;Woodruff et al, 2013;Yagi et al, 2011) could therefore act as a valuable new tool for future studies of these different ADs.…”
Section: Reviewmentioning
confidence: 99%
“…The first study to do so in the context of AD was an allelic series of PSEN1. Woodruff et al knocked in the PSEN1ΔE9 mutation into a control background using TALEN-mediated genome editing (Woodruff et al, 2013). The PSEN1ΔE9 mutation causes a loss of exon 9 and the ability of PSEN1 protein to undergo endoproteolysis to its mature form (Perez-Tur et al, 1995).…”
Section: Published Ipsc Modelsmentioning
confidence: 99%
“…In one such study, PS1 mutation was found to affect the γ-secretase function but not other functions of PS1. Therefore, the mutational effect is a mixture of loss of and gain of functions (Woodruff et al, 2013). In another study, Aβ42/ Aβ40 ratio was found to be higher in the PS1 mutant NPC.…”
Section: Ipsc Technology In Ad Researchmentioning
confidence: 97%